(untitled) (Fiep Bulletin - online, 2011)
The obesity is considered an important problem of public health, and in agreement with OMS (2004) it is had as a global epidemic. The most serious and preoccupying aspect is the increase of the infantile obesity, that he/she will translate himself, in a prevalence still more discharge of adult obesity. Colavitti (2004) it appears that today in the world more than 1 billion people are with weight excess and of these they are 300 million people with obesity, and associate the a series of serious diseases, as heart problems, diabetes, hypertension and also associates the some cancer type. The education is conceived today as one of the factors progressive responsible by the change and orientation of an entire society. And the teaching inside of that context it is characterized by the transformation and development of the intellectual capacities of the discentes addressed to the domain of the knowledge, abilities and his/her application, seeking to reach certain results in the future life (LIBANÊO 2005). This study had the objective of identifying the students’ of the fundamental teaching knowledge about the obesity, noticing as the school deals with this matter, as well as the school Physical education. As methodology was used the field research, and as instrument for collection of data application of a questionnaire in the school with 60 students of the 8th and 9th year of the fundamental teaching, looking for to identify the school and the Physical education treats on the theme of the Obesity with the students. It is concluded that the participant students of this research in her great majority understand partially about the obesity, however the obtained information were not acquired in the school.